2022
DOI: 10.1037/trm0000355
|View full text |Cite
|
Sign up to set email alerts
|

The effect of military service and trauma exposure on resilience.

Abstract: Research suggests that military personnel are more resilient than civilians, but there are few studies on why this may be. Resilience may be a function of simply being a soldier (e.g., via selection or training) or may be a result of surviving traumatic experiences inherent in the job. However, there is little research into the degree to which military status and trauma exposure influence resilience. In this study, we address this by examining the effects of military service membership and trauma exposure on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This transition can be a stressful and sometimes even traumatic experience (Ismaeel et al, 2018;Nakkas, et al, 2016;Sefidan et al, 2021). Aside from being exposed to combat trauma, military personnel are also subject to additional stresses as a result of their training and lifestyle in the military (Sanborn et al, 2022). Stress can be caused by the new social environment, adjustment to strict regiments, strenuous training, and rapid changes in roles (Yan et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This transition can be a stressful and sometimes even traumatic experience (Ismaeel et al, 2018;Nakkas, et al, 2016;Sefidan et al, 2021). Aside from being exposed to combat trauma, military personnel are also subject to additional stresses as a result of their training and lifestyle in the military (Sanborn et al, 2022). Stress can be caused by the new social environment, adjustment to strict regiments, strenuous training, and rapid changes in roles (Yan et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The studies related to soldier resilience can therefore be found. Additionally, it is clear that there is a need to better understand the relationships between different clusters of intrapersonal and interpersonal variables associated with psychological resilience and determine those that contribute most to the soldier's decision to stay and continue to serve in the army wherein the exposure to trauma and adversity is an inevitable part of military life [40].…”
Section: Research Focus and Hypothesesmentioning
confidence: 99%
“…Surprisingly, there have been limited studies that have examined whether there are differences in resilience between military and civilian individuals. The few studies that have compared the two groups have found inconsistent results (e.g., support: Sanborn et al., 2021—US psychological operations Army brigade to community college students; no support: Sohail & Ahmad, 2021—convenient samples of military personnel and civilians in Pakistan). There are some compelling reasons why military personnel might be more resilient such as personnel selection, military culture, unit cohesion, sense of control and agency during high stress events, and access to resilience training in the military (Jex et al., 2013).…”
Section: Introductionmentioning
confidence: 99%